2014
DOI: 10.1007/s10072-014-1755-z
|View full text |Cite
|
Sign up to set email alerts
|

Riboflavin and migraine: the bridge over troubled mitochondria

Abstract: Brain energy metabolism has been found to be disturbed in migraine. A mitochondrial defect may reduce the threshold for migraine attacks both increasing neuronal excitability and leading migrainous brain to a hyper-responsiveness to triggering stimuli. Riboflavin, a major co-factor in oxidative metabolism, may overcome this impairment. RCT studies in adult confirmed that riboflavin is safe and probably effective in migraine prophylaxis, based on level B evidence. Improving brain energy metabolism may reduce th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 21 publications
0
35
0
Order By: Relevance
“…RCT studies in adults has confirmed that riboflavin is safe and probably effective in migraine prophylaxis, based on level B evidence. The bridge is troubled mitochondria, Riboflavin, a major co-factor in oxidative metabolism, may overcome this impairment (Colombo et al, 2014). Riboflavin may be a preventative medication for paediatric migraine (O'Brien and Hershey, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…RCT studies in adults has confirmed that riboflavin is safe and probably effective in migraine prophylaxis, based on level B evidence. The bridge is troubled mitochondria, Riboflavin, a major co-factor in oxidative metabolism, may overcome this impairment (Colombo et al, 2014). Riboflavin may be a preventative medication for paediatric migraine (O'Brien and Hershey, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, in a 31 P‐MRS study at 3 tesla, Reyngoudt et al documented a decrease in phosphocreatine and adenosine triphosphate concentrations in a sample of migraine without aura patients compared to control subjects, thus supporting the hypothesis of mitochondrial dysfunctions in migraine subjects. Furthermore, the literature data suggest the possible efficacy in migraine preventive treatment of riboflavin, a precursor of flavin mononucleotide and flavin adenine dinucleotide, playing a key role in the mitochondrial electron transport chain, and Coenzyme Q10, a small hydrophobic substance acting as an electron carrier in the mitochondrial respiratory chain …”
mentioning
confidence: 99%
“…The hypothesis of the mitochondrial component in migraine neurobiology has been supported in several studies, 32, 33, 34, 35, 36, 37 suggesting that an impairment of the mitochondrial oxidative metabolism, which ultimately causes energy failure in neurons and astrocytes, triggers migraine mechanisms. Furthermore, different types of assays performed in migraine sufferers have shown a decreased activity of the respiratory chain enzymes 33 and a correlation between the extent of the energy disturbance (low ATP levels), and the clinical phenotype severity.…”
Section: Discussionmentioning
confidence: 91%